Monitoring Antiepileptic Drugs: A Level-Headed Approach - St. Louis, Erik K. (Current Neuropharmacology, 2009)
Despite advances in epilepsy therapeutics, some physicians feel uncomfortable with newer antiepileptic drugs (AEDs) due to difficulty in promptly obtaining blood levels to guide medication adjustment, and even when levels for newer AEDs are obtained, many practitioners feel they are not very useful. Lacking confidence in AEDs whose levels that cannot readily or expeditiously be measured, many clinicians share uncertainty about proper use of the newer AEDs and monitoring AED administration. Similarly, some epilepsy patients inflate the importance of AED blood level monitoring, feeling that blood levels falling within traditionally therapeutic ranges are a fail-safe for seizure control, regardless of their compliance or personal behavior aggravating seizure burden, such as poor sleep or use of illicit substances. This review examines the elusive concept of therapeutic AED blood levels and potential uses and abuses of blood level monitoring, reinforcing appropriate uses for blood levels to ensure compliance and adjust for altered AED pharmacokinetics in the context of aging and disease states, pregnancy, or drug interactions.
Keywords: Epilepsy